Relationship between development of cracks, changes of substructure and strains state of tungsten irradiated by plasma heat loads relevant to ITER transient events - Bazdyreva, S.V.; Makhlaj, V.A.; Malykhin, S.V.; Pugachоv, A.T. (Вопросы атомной науки и техники, 2014)
A paper reported the results of changes of structure and stressed state in tungsten targets irradiated by hydrogen plasma in quasi-stationary accelerator QSPA Kh-50 with heat loads relevant to ITER Edge Localized Modes (ELM). The pulsed plasma heat loads with duration of 0.25 ms and energy density up to 0.45 MJ m-2 was applied. Maximum number of irradiating pulses achieved 150. The correlation between the structure, substructure the stressed state of the surface layers changing and cracking processes occurring as results of plasma irradiation was studied. The effect of excess vacancies and vacancy complexes in formation of the crack nucleation at the stage of the residual compressive macro-stress annealing in the initial structure was evaluated. The initial dislocation density is determined by the development of internal stresses and the cracking process in the target surface layers.
PACS: 52.40.Hf Представлены результаты изменения структуры, субструктуры и напряжённого состояния вольфрамовых мишеней, облученных водородной плазмой на квазистационарном ускорителе КСПУ Х-50, с тепловыми нагрузками, близкими к ИТЭР ELM. Применялась импульсная плазменная тепловая нагрузка с длительностью импульса 0,25 мс и плотностью энергии до 0,45 МДж/м2. Максимальное число облучающих импульсов достигало 150. Изучена взаимосвязь между изменением структуры, субструктуры, напряжённого состояния поверхностных слоёв и процессов растрескивания в них, происходящих вследствие плазменного облучения. Установлена определяющая роль избыточных вакансий и вакансионных комплексов в образовании зародышей трещин на стадии отжига остаточных макронапряжений сжатия исходной структуры. Определен вклад исходной плотности дислокаций в развитие внутренних напряжений и процессов растрескивания поверхностных слоёв мишеней. Представлено результати зміни структури, субструктури та напруженого стану вольфрамових мішеней, опромінених водневою плазмою на квазістаціонарному прискорювачі КСПУ Х-50, з тепловими навантаженнями, близькими до ІТЕР ELM. Застосовувалось імпульсне плазмове теплове навантаження з тривалістю імпульсу 0,25 мс і густиною енергії до 0,45 МДж/м2. Максимальне число імпульсів опромінення становило 150. Вивчено взаємозв'язок між зміною структури, субструктури, напруженого стану поверхневих шарів і процесів розтріскування в них, що відбуваються внаслідок опромінення. Встановлена визначальна роль надлишкових вакансій і вакансійних комплексів в утворенні зародків тріщин на стадії відпалювання залишкових макронапружень стиснення вихідної структури. Визначено внесок вихідної густини дислокацій в розвиток внутрішніх напружень і процесів розтріскування поверхневих шарів мішеней.